Identifikasi lithium tanah di kawasan pegunungan selatan DIY - Djoko Mulyanto; R. Agus Widodo (Universitas Pembangunan Nasional Veteran Yogyakarta, 2017)
The diversity of lithology and land conditions such as rainfall, slope /and shape the face of the land has given rise to the diversity of soil properties. Gunungkidul until recently held the record for the highest suicide cases in Indonesia, and the handling of local governments focused on the social problem, cultural and economic pressure that was not the reducing of the problem. In medicine the role of lithium is very strategic to handle patients with multiple personality disorder (bipolar disorder) are likely to commit suicide. Therefore, the authors are very interested in examining the soil lithium concentration in this region. The purpose of this study was to know the concentration of lithium of soil at various lithologies in the region of Gunungkidul. Research using the survey method and purposive sampling using land units map which the results of overlay of geological and slope maps. Lithium is obtained by extracting soil by using strong acids, reading the results by the AAS, lithium analyzed is the soil total Li. The results showed that soil Li total varies quite well to the kinds of rocks, slope and rainfall in the range of 5 - 22 ppm. Generally indicates that the more of slope, the higher the rainfall shows the range of Li is the lower value. The most unique is that the environment of carbonate rocks, soil Li concentration is not affected by environmental conditions, even in the region Li accumulation of rocks to the soil is the highest in comparison with non-carbonate rocks lithology. While the results of water analysis in several areas in Gunungkidul almost all show the value of <0.01 ppm, except in areas of Gedangsari analyzed <0.1 ppm. The concentration indicates that the status of Li ground water in the region of Gunungkidul is very low.